Mapping workshop learning to graduate attributes for Civil Engineering Surveying - Anwar, Faisal; Awange, Joseph; Arora, Balwinder; Nikraz, Hamid; Walker, John (The Engineering & Science Education Research (ESER) & Swinburne University of Technology, 2012)
One of the core units for 2nd year civil engineering students at Curtin University is Civil Engineering Methods 267 (Civil Engineering Surveying), where the students are currently expected to attend lectures and field practicals. These lectures and practicals are aimed at obtaining sufficient learning outcomes that address Curtin’s graduate attributes. Previously, it was only one-hour lecture per week which did not provide required learning outcomes because of the practical nature of the unit. Realizing this, a two-hour workshop per week was introduced in 2009 to provide field training and computational skills. But until now, no study has been carried out to assess whether the workshop learning addresses the graduate attributes.